Postmodern urbanism and architecture, whim or need? - Consiglieri Nieri de Chackal, Marissa (Universidad de Lima. Carrera de Arquitectura, 2019)
Even though there are some characteristics that distinguish postmodern urbanism and architecture, the trend is difficult to understand and it often prompts questioning its validity. This paper aims to demonstrate how and why the postmodern tendency, where current urbanism and architecture develop, represents an important part of the solution to the problems that trouble the world and is therefore a need. For that purpose, two fundamental texts of the movement that lead out to a new architectural reality will be analyzed: Complexity and Contradiction in Architecture by Robert Venturi, and Building Dwelling Thinking by Martin Heidegger.